The Role of Land Certification in Reducing Gender Gaps in Productivity in Rural Ethiopia - Mintewab Bezabih; Stein Holden; Andrea Mannberg (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2012)
This paper analyses the impact of a low cost and restricted rights land certification program on the productivity of female-headed households. The analysis is based on plot level panel data from the East Gojjam and South Wollo Zones in the Amhara region of Ethiopia. The results suggest a positive and significant effect of certification on plot-level productivity, particularly on plots rented out to other operators. In addition, the results show that certification has different impacts on male and female productivity with female-headed households gaining significantly more and with zonal differences in the effectiveness of certification impacts.
Keywords: D02; Q12; Q15; 330; Ethiopia; Female Headed Households; Productivity; Land Market; Certification